Dress and emancipated women in the narrative of Emilia Pardo Bazán - Rodríguez Garabatos, Blanca Paula (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The theme of Fashion and costumes is for Emilia Pardo Bazán inexhaustible whether from a hygienic, moral, economic, social or purely practical point of view. The Galician author lives intensely fashion and her trips abroad keep her in constant contact with the capital of the fashion world and her creations. That is why his novels and stories are full of characters built through fashion. The independent women who populate their stories and novels defy the codes of conduct of the time by dressing in a comfortable and practical way. The author elaborates the psychology of new and modern female literary archetypes such as Fé Neira, Miss Annie and Espina Porcel from clothing, makeup and accessories.
Keywords: comparative literature; fashion; Pardo Bazán; narrative; unpublished letters